MIXED SENTENCE TYPES (Intent Research Scientific Journal, 2024)
In effective writing, varying one's sentence structures purposefully is crucial for maintaining reader engagement and flow. While some argue for consistency in sentence type for stylistic reasons, intentionally incorporating a diversity of structures affords numerous advantages. By mixing between simple, compound, complex and compound-complex constructions, an author can achieve different rhetorical aims and better suit the natural cadences of thought. Rather than adhere rigidly to a single pattern, purposeful variation yields writing that is more dynamic, compelling and reflective of how human cognition actually operates.